Car bułgarski Piotr (927-969) w bizantyńskiej historiografii X-XII wieku - Leszka, Mirosław (Vox Patrum, 2018)
Byzantine historians tied Peter primarily with the establishment of the lasting peace with the Empire in 927. In the sources that present the events from before the reign of the emperor Nikephor Phokas (963-969), when the relations between both states deteriorated, Peter is commonly portrayed as a peacemaker, a deeply religious man, accepting of the Byzantine way of understanding the role of the ruler in religious matters. However, Byzantine authors point out that Peter was able to successfully secure his position and ruthlessly deal with his enemies. The sources describing the events from the last years of his reign portray him as a prideful person, daring to stand up against the Byzantine basileÚj, and who gets rightfully and severely punished for his actions. It should be noted that most often the Byzantine authors did not describe their attitude towards Peter, and did not judge him directly. This results in the reader having to build the image of the Bulgarian ruler himself, based on how the sources describe the events concerning his reign.